Pengaruh Penambahan Gula dan Tepung Terigu pada Media Tanam Dasar terhadap Pertumbuhan dan Hasil Jamur Tiram (Pleurotus ostreatus) - REZKY, PUTRI; PRADNYAWATHI, NI LUH MADE; DARMAWATI, IDA AYU PUTRI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.11, No.4, Oktober 2022, 2023)
The Effect of Sugar and Flour Addition into the Basic Planting Media on the Growth and Yield of Oyster Mushrooms ( Pleurotus ostreatus ) The purpose of this study was to get the best composition from the addition of sugar and wheat flour to the basic growing media for the growth and yield of oyster mushrooms. The research was conducted from May to October 2020 at the UPTD Balai Benih Induk Tanaman Pangan dan Hortikultura, Desa Luwus , Tabanan, Bali. This study used a Complete Randomized Design (CRD) of one factor, namely the mixed material of the planting media. The treatment in this study consisted of: basic planting media with added sugar and wheat flour (sawdust, bran, chalk, sugar, and wheat flour), basic planting media with added sugar (sawdust, bran, chalk, and sugar), basic planting media with the addition of wheat flour (sawdust, bran, chalk, and wheat flour) and basic planting media (sawdust, bran, and chalk). According to the results of research and analysis, it can be concluded that the addition of granulated sugar to the basic planting media of oyster mushroom caused the growth of the mycelium was longer and the size of the hood and the length of the stalk was smaller. The addition of wheat flour to the basic planting media caused the number of oyster mushroom fruit bodies to be less, but has a large hood size. The addition of granulated sugar and wheat flour to the basic growing media of oyster mushrooms caused in a faster total growth time of the mycelium, larger hood size and stalk length, but has fewer fruit bodies and a light wet weight.